Tracking Sleep, Temperature, Heart Rate, and Daily Symptoms Across the Menstrual Cycle with the Oura Ring in Healthy Women - Alzueta E; de Zambotti M; Javitz H; Dulai T; Albinni B; Simon KC; Sattari N; Zhang J; Shuster A; Mednick SC; Baker FC (Dove Medical Press, 2022)
Elisabet Alzueta,1 Massimiliano de Zambotti,1 Harold Javitz,2 Teji Dulai,1 Benedetta Albinni,1,3 Katharine C Simon,4 Negin Sattari,4 Jing Zhang,4 Alessandra Shuster,4 Sara C Mednick,4 Fiona C Baker1,5 1Center for Health Sciences, SRI International, Menlo Park, CA, USA; 2Division of Education, SRI International, Menlo Park, CA, USA; 3Department of Psychology, University of Campania L. Vanvitelli, Italy; 4Department of Cognitive Science, University of California, Irvine, CA, USA; 5School of Physiology, University of the Witwatersrand, Johannesburg, South AfricaCorrespondence: Fiona C Baker, SRI International, 333 Ravenswood Avenue, Menlo Park, CA, 94025, USA, Email Fiona.baker@sri.comBackground and Objective: The ovulatory menstrual cycle is characterized by hormonal fluctuations that influence physiological systems and functioning. Multi-sensor wearable devices can be sensitive tools capturing cycle-related physiological features pertinent to women's health research. This study used the Oura ring to track changes in sleep and related physiological features, and also tracked self-reported daily functioning and symptoms across the regular, healthy menstrual cycle.Methods: Twenty-six healthy women (age, mean (SD): 24.4 (1.1 years)) with regular, ovulatory cycles (length, mean (SD): 28.57 (3.8 days)) were monitored across a complete menstrual cycle. Four menstrual cycle phases, reflecting different hormone milieus, were selected for analysis: menses, ovulation, mid-luteal, and late-luteal. Objective measures of sleep, sleep distal skin temperature, heart rate (HR) and vagal-mediated heart rate variability (HRV, rMSSD), derived from the Oura ring, and subjective daily diary measures (eg sleep quality, readiness) were compared across phases.Results: Wearable-based measures of sleep continuity and sleep stages did not vary across the menstrual cycle. Women reported no menstrual cycle-related changes in perceived sleep quality or readiness and only marginally poorer mood in the midluteal phase. However, they reported moderately more physical symptoms during menses (p < 0.001). Distal skin temperature and HR, measured during sleep, showed a biphasic pattern across the menstrual cycle, with increased HR (p < 0.03) and body temperature (p < 0.001) in the mid- and late-luteal phases relative to menses and ovulation. Correspondingly, rMSSD HRV tended to be lower in the luteal phase. Further, distal skin temperature was lower during ovulation relative to menses (p = 0.05).Conclusion: The menstrual cycle was not accompanied by significant fluctuations in objective and perceived measures of sleep or in mood, in healthy women with regular, ovulatory menstrual cycles. However, other physiological changes in skin temperature and HR were evident and may be longitudinally tracked with the Oura ring in women over multiple cycles in a natural setting.Keywords: sleep, wearables, menstrual cycle, ovulation, body temperature, women's health